2017
DOI: 10.1002/2017wr021215
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Controls of the Surface Water Balance Over Land: Insights From a Systematic Review and Meta‐Analysis

Abstract: The long‐term surface water balance over land is described by the partitioning of precipitation (P) into runoff and evapotranspiration (ET), and is commonly characterized by the ratio ET/P. The ratio between potential evapotranspiration (PET) and P is explicitly considered to be the primary control of ET/P within the Budyko framework, whereas all other controls are often integrated into a single parameter, ω. Although the joint effect of these additional controlling factors of ET/P can be significant, a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(129 citation statements)
references
References 132 publications
(213 reference statements)
14
110
5
Order By: Relevance
“…In addition, the Budyko curve can be represented with evapotranspiration ET/P as a function of ϕ (Figure a). In the present research, we used an analytical solution to the Budyko framework following previous research by Padrón et al () to calculate ω parameter. This analytical equation is derived by combining dimensional analysis and mathematical reasoning as follows: []italicETtrue¯trueP¯=1+[]ϕtrue¯1+[]ϕtrue¯ω1ω, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Budyko curve can be represented with evapotranspiration ET/P as a function of ϕ (Figure a). In the present research, we used an analytical solution to the Budyko framework following previous research by Padrón et al () to calculate ω parameter. This analytical equation is derived by combining dimensional analysis and mathematical reasoning as follows: []italicETtrue¯trueP¯=1+[]ϕtrue¯1+[]ϕtrue¯ω1ω, …”
Section: Methodsmentioning
confidence: 99%
“…The ω can be interpreted thus: the higher the ω is, the higher the favorability of the ET condition is. In other words, pixels with the same value of ϕ but with higher ω parameter have land cover conditions that favor ET over runoff (Padrón et al, ). The aridity index ( ϕ ) values and the ω parameters were calculated from GLDAS V2.0 using 63 years of data sets (from 1948 to 2010) on a global scale (Figure b).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the sensitivity of annual runoff to forest cover changes tends to attenuate as the watershed size increases in large watersheds, and water‐limited watersheds are more sensitive than energy‐limited watersheds (M. Zhang et al, ). However, Padrón et al () found less influence of land cover and direct human interventions on the spatial variability of the partitioning of precipitation into evapotranspiration than frequently hypothesized in the literature.…”
Section: Introductionmentioning
confidence: 91%
“…Aridity is commonly regarded as the main driver of water partitioning at the land surface (Budyko, 1974;Hrachowitz et al, 2013). The influence of climate on hydrological regimes (Berghuijs et al, 2014) and the water balance (Padrón et al, 2017) is well acknowledged, yet it is debated whether this influence is direct, via the water balance, or indirect, via the long-term influence of climate on the landscape (Harman & Troch, 2014). Importantly, climatic variables do not only drive current but probably also trends induced by climate change (Rice et al, 2016).…”
Section: 1029/2018wr022606mentioning
confidence: 99%